Numerical simulations to improve the use of under sleeper pads at transition zones to railway bridges. (1st June 2018) - Paixão, André; Varandas, José Nuno; Fortunato, Eduardo; Calçada, Rui
Graphical abstract: Highlights: A railway track transition zone to a bridge using Under Sleeper Pads (USP) is presented. Receptance tests and field measurements as trains passed by were carried out. Advanced 3D FEM numerical models were calibrated and validated with the experimental data. Dynamic train-track interaction simulations allowed proposing an improved transition design. Results highlight the benefit of USP to mitigate forces and vibrations on the ballast, though careful design is required. Abstract: Transition zones to bridges and other structures are critical locations in railway tracks that frequently evidence poor long-term performance. Under sleeper pads (USPs) are reported to reduce ballast degradation and control the vertical stiffness of the track, which suggests that USPs can contribute to mitigating the frequent negative effects associated with transitions zones. Aiming at understanding in greater depth the influence of USPs on the dynamic behaviour of transition zones and at improving the design of such railway structures, the authors have developed an extensive experimental and numerical study. 3-D FEM models using state-of-the-art numerical approaches were successfully calibrated and validated using experimental measurements. Simulations supported previous findings, highlighting the potential benefit of USPs and pointing to the need to careful designing of the resilient properties of USPs and their arrangement along transition zones, so as to avoid introducing abrupt variations in track vertical stiffness.